Secondary neoplasms in survivors of pediatric acute lymphoblastic leukemia and lymphoblastic lymphoma: a single-center, retrospective study - Ushida, Eri; Toyoda, Hidemi; Kohso, Atsushi; Okumura, Yosuke; Niwa, Kaori; Ito, Takahiro; Morimoto, Mari; Hanaki, Ryo; Amano, Keishiro; Iwamoto, Shotaro; Deguchi, Takao; Hori, Hiroki; et al. (Frontiers in Pediatrics, 2025)
BackgroundAcute lymphoblastic leukemia (ALL)-based therapeutic regimens have markedly improved the survival of children with ALL and lymphoblastic lymphoma (LBL). However, survivors are at risk of secondary neoplasms. Few studies on such secondary neoplasms have been conducted outside of Europe and the United States. The aim of this study was to evaluate the incidence of, risk factors for, and outcomes of secondary neoplasms in long-term survivors of ALL and LBL at a tertiary pediatric oncology center in Mie prefecture, Japan.ProcedureWe retrospectively reviewed 188 patients with ALL and LBL who were treated with an ALL-based therapeutic regimen at Mie University Hospital from January 1, 1977 to December 31, 2022 and followed up.ResultsTen patients developed secondary neoplasms, with 10-year and 20-year cumulative incidences of 2.9% [standard error (SE) = 1.5%] and 5.5% (SE = 2.3%), respectively. The median interval between the primary-cancer diagnosis and secondary-neoplasm diagnosis was 18.5 years (range: 7.8–41.7 years). All 10 secondary neoplasms were central nervous system (CNS) tumors (6 meningiomas and 4 high-grade gliomas). Radiotherapy (p = 0.007) and CNS involvement in the primary cancer (p < 0.001) increased the risk of secondary neoplasms among long-term survivors. Gliomas occurred significantly earlier than meningiomas (p = 0.047), and three patients died of secondary neoplasms (all gliomas).ConclusionsAs secondary gliomas occurred earlier than meningiomas and are associated with poor outcomes, physicians should take great pains to minimize their risk to improve long-term survival and quality of life.